2012
DOI: 10.2337/dc12-0511
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Incidence of Lower-Extremity Amputations in People With Diabetes in Scotland

Abstract: OBJECTIVETo establish the incidence of nontraumatic lower-extremity amputation (LEA) in people with diabetes in Scotland.RESEARCH DESIGN AND METHODSThis cohort study linked national morbidity records and diabetes datasets to establish the number of people with diabetes who underwent nontraumatic major and minor LEA in Scotland from 2004 to 2008.RESULTSTwo thousand three hundred eighty-two individuals with diabetes underwent a nontraumatic LEA between 2004 and 2008; 57.1% (n = 1,359) underwent major LEAs. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 15 publications
10
95
0
2
Order By: Relevance
“…Our data were obtained in [2003][2004], and the incidence of lower-extremity amputation in patients with diabetic foot ulcers has decreased since then in several countries (28). However, studies have observed that the relative risk of amputation for these patients has not changed (29,30), which is why we believe our results are still valid and applicable.…”
Section: Limitations Of the Current Studymentioning
confidence: 60%
“…Our data were obtained in [2003][2004], and the incidence of lower-extremity amputation in patients with diabetic foot ulcers has decreased since then in several countries (28). However, studies have observed that the relative risk of amputation for these patients has not changed (29,30), which is why we believe our results are still valid and applicable.…”
Section: Limitations Of the Current Studymentioning
confidence: 60%
“…DFI is the leading cause of non-traumatic lower limb amputations. [4][5][6][7] The main aim was to study the DFI which is responsible for increased morbidity, amputations and even mortality in diabetic patients. [8][9][10] Diabetic foot infections were more common (33.33%) in age group of 45-54 years whereas P.C Leung reported 75% infections occurred above the age of 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant reduction of 40% in LEA rates occurred between 2004 and 2008. 11 However, the 2013 Scottish Diabetes Survey shows that the absolute numbers and percentages of diabetes-related foot ulcerations and LEA have increased, although this is attributed to better recording procedures. In England, an analysis of national hospital activity data from 1996 to 2005 found that, although LEAs in people with type 1 diabetes fell, type 2 LEAs increased.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%